2015
DOI: 10.1371/journal.pone.0120857
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor Beta Signaling Is Essential for the Autonomous Formation of Cartilage-Like Tissue by Expanded Chondrocytes

Abstract: Cartilage is a tissue with limited self-healing potential. Hence, cartilage defects require surgical attention to prevent or postpone the development of osteoarthritis. For cell-based cartilage repair strategies, in particular autologous chondrocyte implantation, articular chondrocytes are isolated from cartilage and expanded in vitro to increase the number of cells required for therapy. During expansion, the cells lose the competence to autonomously form a cartilage-like tissue, that is in the absence of exog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 62 publications
(58 reference statements)
3
48
0
Order By: Relevance
“…However, as expected, higher levels of Col I were detected in micromass samples, with M+ significantly higher than all other groups but S+. Consistent with previous studies (Hering et al 1994; Tekari et al 2015), we also note that addition of CM caused significant 4.4- and 23- fold increases in Col I expression in micromass (M+) and static scaffold (S+) samples in comparison to the non-CM-stimulated M− and S− counterparts. No such upregulation was observed in samples maintained in more chondrogenic conditions including Pel, S−, the bioreactor with perfusion, and combined perfusion and OHP.…”
Section: Resultssupporting
confidence: 92%
“…However, as expected, higher levels of Col I were detected in micromass samples, with M+ significantly higher than all other groups but S+. Consistent with previous studies (Hering et al 1994; Tekari et al 2015), we also note that addition of CM caused significant 4.4- and 23- fold increases in Col I expression in micromass (M+) and static scaffold (S+) samples in comparison to the non-CM-stimulated M− and S− counterparts. No such upregulation was observed in samples maintained in more chondrogenic conditions including Pel, S−, the bioreactor with perfusion, and combined perfusion and OHP.…”
Section: Resultssupporting
confidence: 92%
“…In this study, we used PL in the chondrogenic differentiation medium without adding recombinant TGF-β, which is considered a basic and essential factor in chondrogenic differentiation medium [6]. Our results also showed that culturing MSCs in a 3D system as pellets in chondrogenic differentiation medium supplement with 5% PL, without the addition of purified recombinant TGF-β, generated a tissue structure similar to cartilage.…”
Section: Discussionmentioning
confidence: 69%
“…We showed that 5% PL-supplemented medium with other differentiation components, could direct the differentiation of MSCs to chondrocytes, which might be due to a high concentration of TGF-β in PL, since TGF-β is known to play a key role in the triggering of chondrocyte differentiation [6, 9]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because Tgf-B1 can exhibit a chondroprotective effect, especially immediately following an injury, the dose-increased levels of Tgf-B1 could have ameliorated the destructive effects of increased Mmp-13 as TAK-242 concentration was increased [9,23]. Wild-type mice exhibited lower Tgf-B1 levels at all treatment levels, another possible explanation of more advanced OA in this genotype: Mmp-13 increases were not countered by a chondroprotective increase in Tgf-B1.…”
Section: Discussionmentioning
confidence: 91%